Expression and oxidative modifications of plasma proteins in autism spectrum disorders: Interplay between inflammatory response and lipid peroxidation. Issue 11 (27th June 2016) - Cortelazzo, Alessio; De Felice, Claudio; Guerranti, Roberto; Signorini, Cinzia; Leoncini, Silvia; Zollo, Gloria; Leoncini, Roberto; Timperio, Anna Maria; Zolla, Lello; Ciccoli, Lucia; Hayek, Joussef
Abstract : Purpose: A role for inflammation and oxidative stress is reported in autism spectrum disorders (ASDs). Here, we tested possible changes in expression and/or oxidative status for plasma proteins in subjects with ASDs. Experimental design: To evaluate protein expression and protein adducts of lipid peroxidation‐derived aldehyde, analysis of plasma proteins was performed in 30 subjects with ASDs and compared with 30 healthy controls with typical development, using a proteomic approach. Results: Significant changes were evidenced for a total of 12 proteins. Of these, ten were identified as proteins involved in the acute inflammatory response including alpha‐2‐macroglobulin, alpha‐1‐antitrypsin, haptoglobin, fibrinogen, serum transferrin, prealbumin, apolipoprotein A‐I apolipoprotein A‐IV, apolipoprotein J, and serum albumin. In addition, significant changes occurred for two immunoglobulins alpha and gamma chains. Conclusions and clinical relevance: Our present data indicate that an inflammatory response, coupled with increased lipid peroxidation, is present in subjects with ASDs. This information can provide new insight into the identification of potential plasma protein biomarkers in autism.